Histological assessment of potential inferior alveolar nerve injury following osteotomy of the mandibular buccal cortex using a piezoelectric saw: Histological assessment of potential IAN injury - Qadir, Shamal Hassan; Kheder, Khurshid Abubakir; Hassan, Snur M.A. (Cellular and Molecular Biology, 2024)
The present study aimed to evaluate the effect of Piezosurgery on histopathologic features of the inferior alveolar nerve (IAN) damage after osteotomy of the buccal cortex of the mandible using piezoelectric devices in Hamdani sheep. A total of ten healthy mature female sheep were included. Each side of the mandible underwent two different experiments: the first experiment operated directly on the mental nerve by touching and activating the piezo tip on the nerve for ten seconds for the left side and thirty seconds for the right side. In the second experiment, the inferior alveolar nerve was touched by an activated piezo tip inside the mandibular canal for ten seconds on the left side and thirty seconds on the right side. All the nerve samples underwent histopathological evaluation, and the scoring system was performed to assess the nerve structures. Mental nerves exposed to piezo tip for 10 seconds showed mild abnormality including disruption of the perineurium with the endoneurium remaining intact. Mental nerves exposed for 30 seconds showed moderate injury with destruction of the perineurium and moderate degeneration of nerve fibers, nevertheless, the endoneurium remained continuous with normal node of Ranvier. Severe damage of the inferior alveolar nerve was seen after exposure to piezo tip for 10 seconds, which showed sloughing of the perineurium and severe vacuolar degeneration of nerve fibers, partial disruption of the endoneurium; however, the axons were still intact. Inferior alveolar nerves exposed for 30 seconds revealed destruction of the perineurium, marked vacuolar degeneration of nerve fibers, focal damage of axon and loss of endoneurium (axonotmesis). Piezosurgery devices have the potential to cause severe nerve damage during surgery and should be used very carefully.